Minimally invasive procedures in the management of uterine fibroids - Szkodziak, Piotr; Szkodziak, Filip; Trzeciak, Kamila; Czuczwar, Piotr (Menopause Review/Przegląd Menopauzalny, 2017)
Uterine fibroids are benign uterine tumors. In women during the reproductive period, uterine fibroids occur in about 25%, whereas after this time, they are observed in more than 40% of women. In the majority of women (about 20-50%), such tumors do not cause discomfort and do not require treatment. Asymptomatic uterine fibroids usually undergo only regular medical control, whereas symptomatic fibroids are an indication for treatment. Current treatment methods include surgical, pharmacological and minimally invasive treatment. Among the current commonly used methods, there are minimally invasive treatment options, which include Uterine Artery Embolization (UAE), Magnetic Resonance Guided Ultrasound Surgery (MRgFUS), MR-guided High Intensity Focused Ultrasound (MR-HIFU) and Laparoscopic Uterine Artery Occlusion (LUAO). The minimally invasive Ultrasound-guided High Intensity Focused Ultrasound method (US-HIFU) is new, but still experimental. The use of MRgFUS/MR-HIFU for the thermoablative treatment of fibroids was approved by the FDA (Food and Drug Administration) in 2004. As a minimally invasive method, it enables preservation of the uterus and eliminates the need for general anesthesia. LUAO is based on the use of the vascular clip, which is placed on the uterine artery at the level of the internal iliac artery. This procedure is performed bilaterally. The use of UAE in obstetrics and gynecology was first described in 1987 as an effective method in the treatment of hemorrhage, which allows avoiding surgical intervention and enables the uterus to be preserved. An appropriate qualification of patients is crucial for high clinical efficacy and prevention of complications after UAE. The candidates should be women with symptomatic uterine fibroids, without other pathologies within the pelvis, who do not plan to get pregnant in the future. The variety of uterine fibroids as for the location, size, and symptoms they can evoke, has enforced a very individual approach to each patient, to begin with observation and regular gynecological control, through a number of pharmacological and minimally invasive treatment methods, and ending with the removal of the uterus. It gives the doctors the tools, which, if used properly, can manage uterine fibroids and fulfil the expectations of the patient.